Pemanfaatan lahan tidak produktif dengan penanaman aneka tanaman buah-buahan di Desa Nyogan Muaro Jambi - Anis Tatik Maryani; Fetty Febriasti Bahar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Fruit crops (mango and avocado) are one of the horticultural commodities of high economic value that have the opportunity to be developed to increase income for villagers. Fruit crops (mango and avocado) with vegetative propagation (graft and grafting) begin to bear fruit at the age of between 2-3 years. Observation results from the village’s potential shows that in Nyogan Village is suitable for the cultivation of mango and avocado plants as a result of graft propagation and grafting. On this basis, it is possible if applied to idle land that is no longer used (on unproductive land). Fruit crops are very likely to be developed on community lands around residential or vacant plantations that have not been so far. Evaluation results show that mango and avocado plants are well known in Nyogan Village but have not been cultivated with well and the seeds used are still obtained conventionally. After the introduction of graft propagated seedlings and the connections and prospects of these plants, the community especially farmers became interested. On this basis, fruit crops are very likely to be developed on community lands that are in the vicinity of housing or vacant plantation lands that have not been utilized to be productive and have added economic and ecological value.